Answer:
1) The determinant = 65
2) The determinant = 152
Explanation:
Let us show how to find the determinant of a matrix
You can find the determinant of this Matrix
![\left[\begin{array}{ccc}a&b&c\\d&e&f\\g&m&n\end{array}\right]](https://img.qammunity.org/2021/formulas/mathematics/college/92j73bl6pmozkh96yltflt2q77qreoxb97.png)
by using this rule
Determinant = a(en - fm) - b(dn - fg) + c(dm - eg)
Let us use this rule with the given matrices
1)
![\left[\begin{array}{ccc}1&-1&3\\2&5&0\\-3&1&2\end{array}\right]](https://img.qammunity.org/2021/formulas/mathematics/college/pvinqozo6ba4wxmjbu73pz0ry20rx35naf.png)
The determinand = 1[(5)(2) - (0)(1)] - (-1)[(2)(2) - (0)(-3)] + 3[(2)(1) - 5(-3)]
= 1[10 - 0] - (-1)[4 - 0] + 3[2 - (-15)]
= 1[10] + 1[4] + 3[2+15]
= 10 + 4 + 3[17]
= 10 + 4 + 51
= 65
The determinant = 65
Let us do the second one
2)
![\left[\begin{array}{ccc}-1&-8&2\\9&1&0\\4&1&2\end{array}\right]](https://img.qammunity.org/2021/formulas/mathematics/college/msdrfvou0ck9m4s468gugnczlb9zc1ejhk.png)
The determinand = -1[(1)(2) - (0)(1)] - (-8)[(9)(2) - (0)(4)] + 2[(9)(1) - 1(4)]
= -1[2 - 0] - (-8)[18 - 0] + 2[9 - 4]
= -1[2] + 8[18] + 2[5]
= -2 + 144 + 10
= 152
The determinant = 152